PENGEMBANGAN KETAHANAN PANGAN DESA TETEI LANAN UNTUK MENUNJANG KETERSEDIAAN PANGAN DI WILAYAH KABUPATEN BARITO SELATAN - Rinto Alexandro (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2022)
Based on the considerations and results of observations in the Tetei Lanan Village Area with quite convincing potentials, namely, among others, fertile and loose land so that it can be planted with various kinds of loose plants as well as guaranteed waters and minimal disaster geographical conditions produce convincing potential and opportunities to support food availability in the South Barito Regency. However, public awareness is still quite minimal. This makes us think about maximizing 4 (four) potentials that will be a source of inspiration for local residents to realize food security and food availability in the South Barito district. The four potentials are (a) Long bean plants grown in plastic cup media. (b) Pulled kale planted in plastic cup media (c) Chili planted in glass cup media (d) Tarpaulin pond for fish. After carrying out our practices and activities, we are increasingly aware that the potential for food security in Tetei Lanan village is very strong because what we are doing is producing positive results. And hopefully then it can be a source of inspiration for local residents in providing food security and food availability for the South Barito Regency area.